(3GdJVNe h GdcSGO (B:s (3GdCSHGH h GdMdhd hab eHGOF GdGbJUGO GdGSdGej (B/s - (3QLH, hVGM fLjHs ((3YeGf(B: s (3OGQ GdfaGFS(B, s, 2010)
(3eaghe GdJVNe h CfhGYg , CSHGH GdJVNe h BKGQg , GdYdGL GdGbJUGOj GdhVYj ddJVNe h GdYdGL GdGbJUGOj GdGSdGej dg (B.s
(3eQGLY U(B.297s
Keywords: (3GdGbJUGO GdGSdGejs; (3GdJVNe GdeGdjs; (3GdQchO GdGbJUGOjs